PEMANFAATAN MEDIA DAN LINGKUNGAN SEBAGAI SUMBER BELAJARDALAM PEMBELAJARAN IPAS DI SD NEGERI 190 PALEMBANG - Agustini, Siska; Subadia, Ela Anggin (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to describe the implementation of Natural Sciences (IPAS) learning at SD Negeri 190 Palembang based on observations and interviews with fifth-grade teachers and students. The study employed a qualitative descriptive method with data collected through direct observation, in-depth interviews, and documentation. The findings revealed that the teacher implemented contextual learning strategies such as role-playing, group discussions, and simple media use (raffia strings and ecosystem diagrams). The teacher also utilized the school environment as a learning resource, such as the schoolyard for ecosystem examples. The main obstacle was the limited use of technological learning media, which made it difficult for some students to understand abstract concepts. However, students’ responses were generally positive—they felt happy and engaged during interactive learning sessions. This study highlights the importance of teacher innovation in developing active, creative, and enjoyable IPAS learning by optimizing available learning resources.